Consensual improvement actions for the Tuberculosis Control Programme in Pernambuco state, Brazil: an e-Delphi study - Simone Santos Bezerra; Mara Pereira Guerreiro; José Lamartine Soares Sobrinho (AIMS Press, 2019)
Objectives: Tuberculosis (TB) remains a major public health problem, particularly in low and middle-income countries. The aim of this study is to consensualise improvement actions for the Tuberculosis Control Programme of the Pernambuco state (SPTC), Brazil. Methods: Firstly, a preliminary workshop was conducted with experts (n = 8), including key stakeholders and health professionals, to select structure and process indicators pertaining to the tuberculosis control programme. Then, an e-Delphi was carried out with a purposive sample of 11 local TB experts. The first-round questionnaire was comprised of 19 open-ended questions on possible improvement actions, based on programme indicators obtained in the previous stage. In the second-round experts rated each action for relevance and feasibility, using a four-point scale. In the last round the participants rated the actions again, in the light of group's answers. We used published criteria to define consensus at the outset of the study. Key findings: Eighty-nine improvement actions achieved a high degree of consensus in both feasibility and relevance in round three. Eighty-six actions were grouped under 19 structure and process indicators, while three were consideredcross-sectional in scope (i.e. related to more than one indicator). Ten out of the 86 actions obtained at least 70% of ratings on the highest score of the scale both for relevance and feasibility. These included: "Request and availability of sputum pots can be made by any health professional in the health unit". Conclusions: The wide array of actions obtained in this Delphi represent a resource from which local SPTC services can select the actions most suitable for each context. The ten most relevant and feasible actions represent a particularly useful starting point to streamline change and potentially improve programme indicators.